1975
DOI: 10.1037/0021-843x.84.6.637
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention to threatening stimuli and field independence as factors in the etiology of paranoid behavior.

Abstract: To test a theory that selective attention to threatening stimuli induces paranoia, an attempt was made to manipulate attention to threatening and nonthreatening statements among college students and examine the effects on three indices of paranoia. Although manipulation checks indicated that attention was varied in the desired manner, hypothesized results in which selective attention to threatening statements would lead to greater scores on the paranoia measures were not found. However, a measure of field inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Accumulating evidence over the past several decades suggests that information processing is limited in the human visual system when individuals are faced with the task of attending to multiple objects at the same time (Kastner & Ungerleider, 2000). Studies have shown that multiple stimuli can either integrate or compete when they are displayed in the same visual field at a given time (Blum & Barbour, 1979; Fox, 1993; Locascio & Snyder, 1975). Some stimuli are preferentially processed because the brain presumably has been designed to process salient stimuli more so than nonsalient stimuli.…”
Section: Attention and Emotionmentioning
confidence: 99%
“…Accumulating evidence over the past several decades suggests that information processing is limited in the human visual system when individuals are faced with the task of attending to multiple objects at the same time (Kastner & Ungerleider, 2000). Studies have shown that multiple stimuli can either integrate or compete when they are displayed in the same visual field at a given time (Blum & Barbour, 1979; Fox, 1993; Locascio & Snyder, 1975). Some stimuli are preferentially processed because the brain presumably has been designed to process salient stimuli more so than nonsalient stimuli.…”
Section: Attention and Emotionmentioning
confidence: 99%
“…In support of this view, some theorists have claimed that selective focus on threatening stimuli can contribute to the development of paranoid-like responses (e.g., Cameron, 1967; Colby, 1981; Kramer, 1994; Meissner, 1978). Although these studies tell nothing about the direction of causality, Locascio and Snyder (1975) found that normal participants whose attention was directed to threatening statements made more paranoid-like responses in the laboratory than participants whose attention was not directed to these statements. Finally, Fenigstein and Vanable (1992) found that paranoid-like cognitions are related to excessive consciousness of the way others perceive, think about, and behave toward the person (public self-consciousness).…”
mentioning
confidence: 94%
“…Most of the social‐cognitive findings in the literature on paranoia have suggested the operation of a paranoid schema or information‐processing bias, which may be sensitive to ambiguous social stimuli and influence the processing of threatening stimuli (Brennan & Hemsley, 1984; Freeman et al , 2002; Locascio & Synder, 1975; Magaro, 1981; Miller & Karoni, 1996; Phillips et al , 2000). Information‐processing biases have been discussed as important factors in the both the development and maintenance of persecutory delusions (Freeman et al , 2002).…”
mentioning
confidence: 99%